EXPORT ORIENTATION OF THE REPUBLIC OF SRPSKA - Здравко Тодоровић, PhD (Acta Economica, 2009)
One of the most common mentioned objectives of economic policy is to increase the exports of the Republic of Srpska. The reasons for this are multiple. First of all, production manifests a high level of import and export dependency, so that the increase in imports is the assumption of increasing production and exports. The swift payment of import their turn requires an increase in exports. Another reason for a sturdy increase in exports is a need to increase foreign currency earnings in order to properly service debt obligations towards abroad. The third important reason for the increase in exports is a high trade deficit, which is formed in the period after year 2000. To implement this important task it is necessary to increase the competitiveness of domestic exports. The first part of this work points to the current tendencies in foreign trade in the countries of Southeast Europe. The second part of the work relates to the scope and structure of the Foreign Trades of the Republic of Srpska. The third part of the work presents institutional measures for the stimulation of exports and substitution of imports in the Republic of Srpska.